RISK FACTORS FOR THE DEVELOPMENT OF LEFT VENTRICULAR MYOCARDIAL HYPERTROPHY IN PATIENTS WITH GOUT - Evgenia Innokentyevna Markelova; V G Barskova; A V Volkov; Yu O Korsakova; E V Ilyinykh (Научно-практическая ревматология, 2012)
Objective — to evaluate potential input of different factors in the development of left ventricular hypertrophy (LVH) in patients with gout. Material and methods. 57 male patients with gout were included into the study. Echocardiography was performed in M- and B-modes and left ventricular myocardial mass index (LVMMI) was calculated for each patient. LVH was defined as LVMMI >115 g/m 2. Results. LVH was detected in 23 (40,4%) out of 57 patients. LVH was associated with advanced age, arterial hypertension, obesity, hyperuricemia and increased C-reactive protein levels.